Environmental and biological monitoring of occupational exposure to polynuclear aromatic hydrocarbons during highway pavement construction in Italy. (1st December 2018) - Fostinelli, Jacopo; Madeo, Egidio; Toraldo, Emanuele; Sarnico, Michela; Luzzana, Giorgio; Tomasi, Cesare; De Palma, Giuseppe
Highlights: Carcinogenic PAHs released by hot mix asphalt are detectable only in the fume phase. 1-Hydroxypyrene is a valid biomarker for biomonitoring of asphalt workers. 2-Naphthol suffers a higher confounding effect by smoking habits. Abstract: Objectives: We performed a cross-sectional study with the main aim of evaluating occupational exposure to polycyclic aromatic hydrocarbons (PAHs) in workers involved in the pavement construction of a new highway in Northern Italy, where modified bitumen was used as binder for Hot Mix Asphalt. Methods: We applied a combined approach of air and biological monitoring. Both the aerosol and vapour phases of bitumen were collected applying the NIOSH 5506 method. The 16 PAHs listed as high priority by EPA were determined by HPLC-UV. End-of-shift urine samples were collected from 144 workers to determine 1-hydroxypyrene (1-OHP) and 2-naphthol (2-NAP) concentrations after enzyme digestion and HPLC-UV analysis. Socio-demographic and lifestyle information was collected by a questionnaire. Results: Paving workers were actually exposed to PAHs, including carcinogenic compounds, that were measurable only in the aerosol phase. Higher exposure as well as dose levels were measured for the paver group. Biological monitoring confirmed that 1-OHP was less affected by smoking habits as compared to 2-NAP and showed a higher association with occupational exposure. Conclusion: Carcinogenic PAH compounds were detectable only in the aerosol phase and this must be taken into account in the adoption of preventive measures. Biomonitoring supported the superiority of 1-OHP as compared to 2-NAP in assessing the internal dose in such workers.